2020
DOI: 10.2147/cmar.s258645
|View full text |Cite
|
Sign up to set email alerts
|

<p>New Advances in Canonical Wnt/β-Catenin Signaling in Cancer</p>

Abstract: Wnt/β-catenin-mediated signaling is a key pathway regulating tissue growth and development, and tumorigenesis, and has received increasing attention in recent years. In addition to participating in healthy tissue and organ development, ectopic activation of the pathway can cause a variety of tumors and other pathologies. The pathway plays a critical role in many processes such as proliferation, differentiation, apoptosis, migration, invasion, epithelial–mesenchymal transition and cancer cell stemness. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 78 publications
1
36
0
Order By: Relevance
“…The Wnt gene was first identified in mice, called Int-1. It is named Wnt because of its high homology with the wingless gene of Drosophila melanogaster 5 , 6 . The Wnt pathway plays an important role in regulating embryonic development and cell differentiation 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wnt gene was first identified in mice, called Int-1. It is named Wnt because of its high homology with the wingless gene of Drosophila melanogaster 5 , 6 . The Wnt pathway plays an important role in regulating embryonic development and cell differentiation 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It is named Wnt because of its high homology with the wingless gene of Drosophila melanogaster 5 , 6 . The Wnt pathway plays an important role in regulating embryonic development and cell differentiation 5 , 6 . Abnormalities in Wnt/β-catenin signaling have been found in many tumors, including NSCLC, and play important roles in cancer progression 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway has been reported to be related to the oncogenesis and progression of multiple kinds of human cancers [ 15 17 ]. β-catenin is considered a positive regulator of this pathway that functions by promoting the transcription of target genes [ 29 ]. Some target genes, such as MMP9 and cyclin D1, are involved in oncogenesis, regulating cancer proliferation and metastasis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoko Katsuno et al research shows that TGF-β signaling and epithelial-mesenchymal transition in cancer progression. Furthermore, Wen et al 39 research indicated that the ectopic activation of Wnt/β-catenin-mediated signaling pathway can lead to a variety of tumors and diseases. This pathway not only plays an important role in proliferation, differentiation, apoptosis, migration, and invasion, but also plays an important role in the invasion and metastasis of cancer in epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%